2011
DOI: 10.1021/jp201002v
|View full text |Cite
|
Sign up to set email alerts
|

The pH-Controlled Plasmon-Assisted Surface Photocatalysis Reaction of 4-Aminothiophenol top,p′-Dimercaptoazobenzene on Au, Ag, and Cu Colloids

Abstract: In this paper, we report experimentally and theoretically a surface photocatalysis reaction of 4-aminothiophenol (PATP) to p,p 0dimercaptoazobenzene (DMAB) on Au, Ag, and Cu colloids. Surface enhanced Raman scattering (SERS) spectra of PATP on Au and Cu colloids are significantly different from the normal Raman spectrum of PATP powder. Quantum chemical calculations reveal that PATP on Au and Cu colloids is converted to DMAB by a surface photocatalysis reaction, and all the strongly enhanced Raman peaks are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
150
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 153 publications
(169 citation statements)
references
References 30 publications
(38 reference statements)
16
150
2
1
Order By: Relevance
“…Since 2010, various experimental and theoretical results have supported the production of DMAB from pATP by plasmon-driven surface-catalyzed chemical reactions. [61][62][63][64][65][66][67][68][69][70][71][72] Adv. Optical Mater.…”
Section: Hot Electron-induced Surface-catalyzed Chemical Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2010, various experimental and theoretical results have supported the production of DMAB from pATP by plasmon-driven surface-catalyzed chemical reactions. [61][62][63][64][65][66][67][68][69][70][71][72] Adv. Optical Mater.…”
Section: Hot Electron-induced Surface-catalyzed Chemical Reactionsmentioning
confidence: 99%
“…Sun et al found that the photocatalytic oxidation reaction cannot occur under the acidic condition (pH = 3); however, such a reaction takes place efficiently under neutral and alkaline conditions (pH = 7 and 10). [72] Following the pioneering studies on plasmon-driven chemical reactions, various intensive studies have continued to be conducted until now. [30,[89][90][91][92][93][94] Wang et al controlled the selectivity of the SPR-mediated photocatalytic oxidation of pATP on AuNPs by charge transfer from UV-excited TiO 2 (Figure 9e).…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…[38][39][40] One of the most promising applications of SPPs, especially localized SPPs, is surface-enhanced Raman scattering (SERS), which has been studied both theoretically and experimentally for many decades. [12][13][14][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] As an optical fingerprint, Raman spectra, which could be used to analyze chemical structures, are widely used in scientific investigations and material analysis. However, as a weak process, the small Raman scattering cross-section makes the detection of a small number of molecules a problem even after the laser power is increased.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency was confirmed by SERS spectroscopy ( Figure S2c) of p-aminobenzenethiol (ABT). [19] To form the sensor, the gold particles inside the capsules were capped with ABT. This molecule was selected because of the thiol group, which can covalently bind to gold, and the amino group, which can diazotize with an equimolecular concentration of NO at an acidic pH value.…”
mentioning
confidence: 99%